Intraskeletal Variability of Relative Cortical Area in Humans. Issue 9 (22nd June 2015) - Stewart, Marissa C.; Goliath, Jesse R.; Stout, Sam D.; Hubbe, Mark
ABSTRACT Histomorphometric and cross‐sectional geometric studies of bone have provided valuable information about age at death, behavioral and activity patterns, and pathological conditions for past and present human populations. While a considerable amount of exploratory and applied research has been completed using histomorphometric and cross‐sectional geometric properties, the effects of intraskeletal variability on interpreting observed histomorphometric data have not been fully explored. The purpose of this study is to quantify intraskeletal variability in the relative cortical area of long bones and ribs from modern humans. To examine intraskeletal variability, cross‐sections of the femur, tibia, fibula, humerus, radius, ulna, and rib when present, were examined within individuals from a cadaveric collection (N = 34). Relative cortical area was compared within individuals using a repeated measurements General Linear Model, which shows significant differences between bones, particularly between the rib and the remaining long bones. Complementarily, correlations between bones' relative cortical area values suggest an important allometric component affecting this aspect of long bones, but not of the rib. This study highlights the magnitude of intraskeletal variability in relative cortical area in the human skeleton, and because the relative cortical area of any particular bone is affected by a series of confounding factors, extrapolation of relative cortical area values to infer load history for other skeletal elements can be misleading. Anat Rec, 298:1635–1643, 2015. © 2015 Wiley Periodicals, Inc.